100 Silent Films. - Dixon, Bryony (BFI screen guides., 2011)
Bryony Dixon's illuminating guide provides a selection of one hundred key films of the silent period (1895-1930), featuring films from a variety of countries, genres and directors, together with an introductory overview and useful filmographic and bibliographic information.